Quality Assessment of Ground Water in Kashmir (International Journal of Innovative Research in Computer Science & Technology, 2022)
The current research examines the quality  of ground water in Kashmir (J&K), India, for human  consumption and other purposes. For water quality testing,  a total of six sampling sites in the research region were  chosen. Pampore, Ganderbal, Batamaloo, Budgam, Sopore,  and Sumbal are the sampling locations. Electrical  conductivity, total dissolved solids (TDS), total suspended  solids, chloride concentration, pH , sulphate content, and  turbidity were used to evaluate water quality in the research  region. The results of the sodium adsorption ratio (SAR)  calculations along with the electrical conductivity suggested  that the ground water in the study area can be used for  irrigation without posing any risk to crop soils. The  analytical data from the research region further reveals that,  with the exception of a few spots, the ground water in the  study area is appropriate for residential use.
Keywords: Ground water; Conductivity; chemical affinity; alkalinity; contamination